The Implementation of Cooperative Learning Strategy of Student Facilitator and Explaining (SFE) Type to Improve Activity and Learning Result - Widayati, Risha Amalia (Classroom Action Research Journal (CARJO), 2018)
A good and balanced learning process will emphasize the mutual interaction between teachers and students by using teaching materials, methods and learning media that exist as learning resources. SFE expects students to understand the material presented by the teacher because the students will later re-explain the material they understand. Using a qualitative approach with Classroom Action Research (CAR). Data were collected by analysis of student activity observation sheet, documentation, field note, pre-test and post-test in every cycle. Data analysis in this research is done by presenting data, reducing data and draw a conclusion. Research procedure through four stages: action planning stage, action implementation, observation, and reflection. The results of the research are; (1) the application of learning with SFE on the economic subjects of class X across the economic interests of SMAN 9 Malang in the first cycle has not run optimally and there are still many shortcomings. In the second cycle, the application runs better where the students have started to be active and conducive; (2) during the learning process with the SFE strategy of active class X students across the economic interests of SMAN 9 Malang increased; (3) during the learning process with SFE learning outcomes of students of class X across the economic interests of SMAN 9 Malang increased; (4) during the learning process with SFE learning outcomes of students of class X across the economic interests of SMAN 9 Malang increased.